Correction: Acquisition and maintenance of disgust reactions in an OCD analogue sample: Efficiency of extinction strategies through a counter-conditioning procedure. - PLOS One Editors (PLoS ONE, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0254592.].